Health profile of the inmates at women prisoner ward, Ranchi: findings of a health camp - Sunderam, Shalini; Kumari, Anju Prabha; Kumar, Satish; Kumari, Gunjan; Kashyap, Vivek (International Journal Of Community Medicine And Public Health, 2021)
Background: There is scanty data revealing the health profile of the female prisoners, so there was a felt need to assess the actual situation inside the prison. Aim and objectives were to obtain the socio-demographic information of the inmates of the women prisoner ward and to assess the health status of the study population. Methods: This cross-sectional study was carried out among the inmates, at central jail Hotwar, Ranchi, on 28th February 2020 during a health checkup camp, conducted by Department of Community Medicine, Rajendra Institute of Medical Sciences, Ranchi. Out of total 102 females residing there, only 59 females participated in the study and were interviewed using pretested semi structured questionnaire. This was followed by general examination. The collected data was entered in Ms Excel sheet and then analyzed. Results: The mean age (SD) of the participants was 23.65(6.02) years. Maximum participants (94.9%) were from Jharkhand, 84.74 % were unmarried and 59.5%of the participants had no formal education. On general examination, 37.28% participants were found anemic and 5.08% were underweight. Conclusions: The present study revealed that majority of the participants residing there are of productive age group. The prevailing health problem is same as of general population and fortunately preventable.